2020
DOI: 10.24018/ejbmr.2020.5.4.452
|View full text |Cite
|
Sign up to set email alerts
|

Analysis Performance of Islamic Bank in Indonesia: Before and After the Spin Off

Abstract: This research is a proof and analytic and experimental concept. This study aims to analyze the performance of Islamic Commercial Banks (BUS) before the spin off compared to the performance after the spin off. An example of this research is a BUS that has done a pure spin off or spin off conversion. Based on the selected sample, obtained 5 BUS that will be taken as research samples, namely BRI Syariah, BJB Syariah, BNI Syariah, Bukopin Syariah, and BTPN Syariah. The performance variable used is to measure using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…The efficiency level of Islamic banks is better after the spin-off than the previous condition (Rusydiana et al, 2019). (Nasuha, 2012;Pernamasari, 2020) show positive differences in performance on five aspects of financial ratios (CAR, NPF, FDR, ROA, and ROE) in spin-off Islamic banks. In addition, there are also differences between before and after the spin-off policy at the asset level (Khairunnisa & Khasanah, 2018) and deposit funds (Taga et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 78%
“…The efficiency level of Islamic banks is better after the spin-off than the previous condition (Rusydiana et al, 2019). (Nasuha, 2012;Pernamasari, 2020) show positive differences in performance on five aspects of financial ratios (CAR, NPF, FDR, ROA, and ROE) in spin-off Islamic banks. In addition, there are also differences between before and after the spin-off policy at the asset level (Khairunnisa & Khasanah, 2018) and deposit funds (Taga et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 78%
“…In the aspect of efficiency, based on the ability to generate income from assets (TATR), it is revealed that BNIS is increasingly efficient [22]. This is confirmed by the results of an increasingly efficient DEA analysis [23,24], although some studies reveal that BRIS is more inefficient than before the spin-off [18,25,26]. Similar conditions were also found in the profitability ratios (NPM and ROA) [18,20,27], asset growth, third party funds, financing [19], market share [22], financing productivity [23], and productivity of social funds management [28].…”
Section: Bank Bni Syariahmentioning
confidence: 85%
“…The financial performance of BNIS has been observed by 11 researchers. BNIS' capital adequacy has increased after the spin-off [18], although many studies have revealed that there is no significant change [19][20][21]. In the aspect of efficiency, based on the ability to generate income from assets (TATR), it is revealed that BNIS is increasingly efficient [22].…”
Section: Bank Bni Syariahmentioning
confidence: 99%
See 2 more Smart Citations